2015
DOI: 10.1007/s00210-015-1159-5
|View full text |Cite
|
Sign up to set email alerts
|

FTY720 and two novel butterfly derivatives exert a general anti-inflammatory potential by reducing immune cell adhesion to endothelial cells through activation of S1P3 and phosphoinositide 3-kinase

Abstract: Sphingosine-1-phosphate (S1P) is a key lipid regulator of a variety of cellular responses including cell proliferation and survival, cell migration, and inflammatory reactions. Here, we investigated the effect of S1P receptor activation on immune cell adhesion to endothelial cells under inflammatory conditions. We show that S1P reduces both tumor necrosis factor (TNF)-α- and lipopolysaccharide (LPS)-stimulated adhesion of Jurkat and U937 cells to an endothelial monolayer. The reducing effect of S1P was reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 59 publications
0
21
0
1
Order By: Relevance
“…16 Apart from induction of lymphopenia, a novel molecular mechanism by which FTY720 exerts anti-inflammatory effect has been reported: suppressing gene transcription of endothelial adhesion molecules and thereby preventing adhesion of immune cells to endothelial cells and subsequent extravasation through activation of S1P3. 58 Our results showed that FTY720 inhibits ICAM-1 and VCAM-1 expression while promoting gene transcription of S1P3 in diabetic rats. We therefore postulate that FTY720 may suppress leukocyte adhesion and subsequent BRB breakdown via up-regulation of S1P3, contributing to its protection in DR.…”
Section: Discussionmentioning
confidence: 74%
“…16 Apart from induction of lymphopenia, a novel molecular mechanism by which FTY720 exerts anti-inflammatory effect has been reported: suppressing gene transcription of endothelial adhesion molecules and thereby preventing adhesion of immune cells to endothelial cells and subsequent extravasation through activation of S1P3. 58 Our results showed that FTY720 inhibits ICAM-1 and VCAM-1 expression while promoting gene transcription of S1P3 in diabetic rats. We therefore postulate that FTY720 may suppress leukocyte adhesion and subsequent BRB breakdown via up-regulation of S1P3, contributing to its protection in DR.…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, C5a triggers the activation of ANCA, thereby activating the coagulation system and producing thrombin [ 48 , 51 ]. Because S1P is a critical factor in C5a-mediated neutrophil activation, it can potentially play a role in the inflammatory and coagulation systems [ 48 , 52 ]. S1P interacts with C5a to cause ANCA-induced neutrophil respiratory bursts and degradation in AAV.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the decrease in neutrophil migration could be explained by the blockade of leukotrienes biosynthesis caused by the 5-lipoxygenase inhibition brought about by the S1P 4 receptor activation [ 27 ]. With regard to the S1P 3 receptor activation, FTY720 has also been demonstrated to downregulate the in vitro expression of adhesion molecules on endothelial cells through S1P 3 via PI3K activation [ 28 ], a feature possibly reducing immune cell transmigration into inflamed areas.…”
Section: Discussionmentioning
confidence: 99%